Pengembangan Media Pembelajaran Interaktif Berbasis Canva Berdasarkan Model Discovery Learning Pada Materi Pengolahan Data - Dwiana May Astiningsih; Naila Tsuraya Zahra; Riska Risma Yanti; Alfiana Nurussama; Teten Ginanjar Rahayu (Jurnal Ilmu Pendidikan Guru Sekolah Dasar dan Usia Dini, 2025)
The development of digital technology demands innovation in mathematics education at the elementary school level, particularly regarding data processing topics, which students still find challenging. Low learning interest and a lack of student engagement in understanding the concepts of mean, median, and mode are issues that need to be addressed through the use of interactive learning media. This study aims to develop and test the validity and practicality of "MEMODI," a Canva-based interactive mathematics learning medium for fifth-grade data processing materials. This study employed the Research and Development (R&D) method using the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects were fifth-grade students at SDN 4 Nagri Kaler. Data collection techniques included validation sheets from material and media experts, as well as student response questionnaires. Data were analyzed using quantitative descriptive techniques by calculating feasibility percentages. The results indicated that the "MEMODI" learning medium achieved a very high validity score, with an average percentage of 92.25%, and a practicality level of 95%, falling into the "very practical" category. The implementation of the medium showed that the use of Canva was able to increase student engagement, facilitate the understanding of mean, median, and mode concepts, and support independent learning through interactive features and direct feedback. Consequently, the Canva-based interactive learning medium "MEMODI" is declared valid, practical, and feasible for use as an alternative mathematics learning medium in elementary schools.